Quarrel technololgy studying of microstructure optic fibers - Филипенко, Александр Иванович; Бакайся, Анастасия Вячеславовна (Eastern-European Journal of Enterprise Technologies, 2009)
The problem of fusion of microstructured optical fibers with single-mode fibers is considered. The basic causes of loss: welding diameter mismatch of mode field and the complete destruction of the air holes are investigated. A variety of ways to connect depending on the structure of microstructured fibers are offered